2009
DOI: 10.1526/003601109789037204
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxes of Providing Rural Social Services: The Case of Homeless Youth

Abstract: Economic and demographic changes in rural areas continue to introduce big-city problems in small towns. These communities' ability and willingness to respond are likely to be influenced by the geography, culture, and array of organizations in rural places. But how these characteristics of rural places shape local response is hard to predict and as yet unexplored. This article reports data from interviews with social-service providers and homeless youth in a rural county in the northwestern United States, drawi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 30 publications
3
44
0
Order By: Relevance
“…However, little anthropological work has been conducted on the topic of homelessness in rural areas, even though this is a growing and serious problem in the US, the UK, Canada and elsewhere (Stover 1999;Cloke and Widdowfield 2000;Whitzman 2006). Research indicates that the incidence and prevalence of homelessness in rural areas is often equal to that found in the city; and similarly includes homelessness that is temporary, episodic and long-term (Edwards, Torgerson, and Sattern 2009;Post 2002;Lawrence 1995). People experiencing homelessness in rural areas frequently suffer other disparities, which often inter-penetrate with homelessness.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, little anthropological work has been conducted on the topic of homelessness in rural areas, even though this is a growing and serious problem in the US, the UK, Canada and elsewhere (Stover 1999;Cloke and Widdowfield 2000;Whitzman 2006). Research indicates that the incidence and prevalence of homelessness in rural areas is often equal to that found in the city; and similarly includes homelessness that is temporary, episodic and long-term (Edwards, Torgerson, and Sattern 2009;Post 2002;Lawrence 1995). People experiencing homelessness in rural areas frequently suffer other disparities, which often inter-penetrate with homelessness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they may not always fall under literal definitions of homelessness that determine eligibility for government programs, inasmuch as they cycle in and out of various housing situations over time. These situations include sleeping in shelters, cars, abandoned buildings, motels, the woods, at a friend's house or brief stays in low-rental accommodation (Edwards, Torgerson, and Sattern 2009). Because homelessness in rural areas is often episodic and homeless people are hidden from public view, they do not have the same visibility as the urban homeless, perhaps explaining the relative lack of scholarly attention to this social issue (Whitzman 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the idyllic view of rural, smaller community life that many people have may render many social problems invisible (Edwards, Torgerson, & Sattem, 2009). For example, surveys of service providers and law enforcement personnel in counties across the United States revealed that professionals in rural communities perceived that commercial sex and sex trafficking did not occur in their communities, citing the difficulty of hiding these activities in smaller communities and the advantage of greater anonymity in larger communities (Newton et al, 2008).…”
mentioning
confidence: 99%
“…For example, surveys of service providers and law enforcement personnel in counties across the United States revealed that professionals in rural communities perceived that commercial sex and sex trafficking did not occur in their communities, citing the difficulty of hiding these activities in smaller communities and the advantage of greater anonymity in larger communities (Newton et al, 2008). Also, collection of data on emerging social problems is more limited in rural communities because individuals perceive the problem to be a metropolitan issue (Edwards et al, 2009). For example, service providers and law enforcement personnel in rural communities were less likely to receive training on human trafficking, and to utilize recordkeeping procedures to distinguish human trafficking victims from other clients they served, compared to professionals in metropolitan communities (Newton et al, 2008).…”
mentioning
confidence: 99%